T3P mediated intramolecular rearrangement of o-aminobenzamide to o-ureidobenzonitrile using isothiocyanates. Issue 8 (18th April 2021) - Shamanth, Sadashivamurthy; Nagarakere, Sandhya C.; Sagar, Kunigal S.; Narayana, Yatheesh; Mamatha, Mahesha; Rangappa, Kanchugarakoppal S.; Kempegowda, Mantelingu
Abstract: Current work describes the environmentally benign approach for the synthesis of o -ureidobenzonitriles, from o -aminobenzamides and isothiocyanates using T3P. Here, the conversion of thiourea to urea and amide to nitrile take place simultaneously via unprecedented intramolecular rearrangement. This protocol is operationally facile and offers wide variety of o -ureidobenzonitriles at room temperature in good to excellent yields. Graphical Abstract: UF0001